THE INFLUENCE OF VIRAL MARKETING AND ONLINE CUSTOMER REVIEWS ON TIKTOK ON PURCHASING DECISIONS FOR UNIQLO FASHION PRODUCTS AMONG GENERATION Z IN INDONESIA : A STUDY OF THE MEDIATING ROLE OF CONSUMER TRUST - Syah, Irchan Ardian; Salim, Muhartini (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
The e-commerce industry in Indonesia has experienced significant growth. Data from the Central Statistics Agency (BPS) shows 17%, with the total number of e-commerce businesses reaching 26.2 million units. This study aims to analyze the influence of viral marketing and online customer reviews on TikTok on the purchase decision of UNIQLO fashion products among Generation Z in Indonesia, considering the mediating role of consumer trust. This study uses quantitative methods by distributing questionnaires to 160 Generation Z respondents who actively use TikTok. This research data was processed using SEM (Structural Equation Modeling) using the SmartPLS4 application. The results show that Viral Marketing has a significant impact on Trust, Online Consumer Reviews has a significant impact on Trust, Trust has a significant impact on Purchasing Decisions, Viral Marketing has a significant impact on purchasing decisions, Viral Marketing has a significant impact on Purchasing Decisions through Trust, Online Consumer Reviews has a significant impact on Purchasing Decisions through Trust. However, the Online Consumer Reviews variable did not significantly affect purchasing decisions. The implication of this research for UNIQLO is that utilizing viral marketing and encouraging positive customer reviews on platforms such as TikTok can be an effective strategy to increase purchase decisions. UNIQLO also needs to communicate values that align with Generation Z preferences, such as sustainability and ethical practices in the fashion industry.